Exopolysaccharides from Bifidobacterium animalis Ameliorate Escherichia coli-Induced IPEC-J2 Cell Damage via Inhibiting Apoptosis and Restoring Autophagy - Lanxin Yuan (MDPI AG, 2021)
Enteropathogenic Escherichia coli (EPEC) is a common zoonotic pathogen that causes acute infectious diarrhea. Probiotics like Bifidobacterium are known to help prevent pathogen infections. The protective effects of Bifidobacterium are closely associated with its secretory products exopolysaccharides (EPS). We explored the effects of the EPS from Bifidobacterium animalis subsp. lactis (B. lactis) on ameliorating the damage of an intestinal porcine epithelial cell line (IPEC-J2) during EPEC infection. Pretreatment with EPS alleviated EPEC-induced apoptosis through the restoration of cell morphology and the downregulation of protein expressions of cleaved-caspase 8, cleaved-caspase 3, and cleaved-PARP. EPS-mediated remission of apoptosis significantly improved cell viability during EPEC infection. EPEC infection also resulted in impaired autophagy, as demonstrated by decreased expressions of autophagy-related proteins Beclin 1, ATG5, and microtubule-binding protein light chain-3B (LC3B) and the increased expression of p62 through western blot analysis. However, EPS reversed these effects which indicated that EPS promoted autophagosome formation. Furthermore, EPS prevented the lysosome damage induced by EPEC as it enhanced lysosomal acidification and raised lysosome-associated protein levels, thus promoted autophagosome degradation. Our findings suggest that the amelioration of EPEC-induced cell damages by EPS is associated with the limitation of detrimental apoptosis and the promotion of autophagy flux.